New Insights into the Skull of Istiodactylus latidens (Ornithocheiroidea, Pterodactyloidea) - Witton, Mark P. (Public Library of Science, 2012)
The skull of the Cretaceous pterosaur Istiodactylus latidens, a historically important species best known for its broad muzzle of interlocking, lancet-shaped teeth, is almost completely known from the broken remains of several individuals, but the length of its jaws remains elusive. Estimates of I. latidens jaw length have been exclusively based on the incomplete skull of NHMUK R3877 and, perhaps erroneously, reconstructed by assuming continuation of its broken skull pieces as preserved in situ. Here, an overlooked jaw fragment of NHMUK R3877 is redescribed and used to revise the skull reconstruction of I. latidens. The new reconstruction suggests a much shorter skull than previously supposed, along with a relatively tall orbital region and proportionally slender maxilla, a feature documented in the early 20(th) century but ignored by all skull reconstructions of this species. These features indicate that the skull of I. latidens is particularly distinctive amongst istiodactylids and suggests greater disparity between I. latidens and I. sinensis than previously appreciated. A cladistic analysis of istiodactylid pterosaurs incorporating new predicted I. latidens skull metrics suggests Istiodactylidae is constrained to five species (Liaoxipterus brachyognathus, Lonchengpterus zhoai, Nurhachius ignaciobritoi, Istiodactylus latidens and Istiodactylus sinensis) defined by their distinctive dentition, but excludes the putative istiodactylids Haopterus gracilis and Hongshanopterus lacustris. Istiodactylus latidens, I. sinensis and Li. brachyognathus form an unresolved clade of derived istiodactylids, and the similarity of comparable remains of I. sinensis and Li. brachyognathus suggest further work into their taxonomy and classification is required. The new skull model of I. latidens agrees with the scavenging habits proposed for these pterosaurs, with much of their cranial anatomy converging on that of habitually scavenging birds.